The Effect Of Profitability, Environmental, Social & Gov-ernance (Esg), And Political Connection On Firm Value - Santosa, Kezia Virginia Elok; Prastiwi, Arum (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
In an unstable global economy, companies must adopt various strategies to sustain their businesses while competing to enhance their value in the eyes of potential investors. A high firm value attracts investors and increases investment opportunities. This study aims to empirically examine the effect of profitability, Environmental, Social, & Governance (ESG), and political connections on firm value. From a population of manufacturing companies listed on the IDX from 2021 to 2023, 90 companies were selected as samples using a purposive sampling technique. The results of multiple regression analysis indicate that profitability significantly affects firm value, while ESG and political connections have no significant effect on firm value. These findings align with the Signaling Theory, which posits that profitability serves as a positive signal to investors, reinforcing the importance of improving profitability to enhance firm value. Thus, potential investors should consider profitability as a key factor in making investment decisions.